2018
DOI: 10.3168/jds.2017-14311
|View full text |Cite
|
Sign up to set email alerts
|

Communications of Staphylococcus aureus and non-aureus Staphylococcus species from bovine intramammary infections and teat apex colonization

Abstract: The role of non-aureus staphylococci (NAS) in the risk of acquisition of intramammary infections with Staphylococcus aureus is vague and still under debate. The objectives of this study were to (1) investigate the distribution patterns of NAS species from milk and teat skin in dairy herds with automatic milking systems, and (2) examine if the isolated NAS influences the expression of S. aureus virulence factors controlled by the accessory gene regulator (agr) quorum sensing system. In 8 herds, 14 to 20 cows wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
29
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 47 publications
8
29
0
2
Order By: Relevance
“…Although the relationship between NAS species causing IMI and those colonizing the teat canal has rarely been quantified (17), a difference in distribution of NAS species between teat canal samples and milk samples was expected. Previous studies found uneven distributions of different NAS species in milk samples and teat apices, including NAS species relevant and less relevant for IMI respectively (8, 16, 27, 31). The teat canal acts as a barrier against invading microorganisms causing IMI and several studies have shown that it harbors several different bacterial species, including Staphylococcus spp., Enterobacteriaceae, Streptococcus spp ., and Clostridium spp .…”
Section: Discussionmentioning
confidence: 90%
“…Although the relationship between NAS species causing IMI and those colonizing the teat canal has rarely been quantified (17), a difference in distribution of NAS species between teat canal samples and milk samples was expected. Previous studies found uneven distributions of different NAS species in milk samples and teat apices, including NAS species relevant and less relevant for IMI respectively (8, 16, 27, 31). The teat canal acts as a barrier against invading microorganisms causing IMI and several studies have shown that it harbors several different bacterial species, including Staphylococcus spp., Enterobacteriaceae, Streptococcus spp ., and Clostridium spp .…”
Section: Discussionmentioning
confidence: 90%
“…However, different Staphylococcus spp. appear to have different roles in relation to the development of this kind of infections [ 28 ]. In this study, we might relate the high abundance in Staphylococcus in Churra milk samples with the reported low microbial diversity value.…”
Section: Discussionmentioning
confidence: 99%
“…About 30 to 40 lactating dairy cows were selected randomly from each herd on the basis of the criteria of having no clinical mastitis, SCC ≥200,000 cells/mL at the preceding milk recording, and not subjected to antibiotic therapy during the 4 wk before sample collection. From each cow with an odd laboratory running number, teat skin swab and aseptic milk samples were taken from right hind and left front quarters (Mahmmod et al, 2018).…”
Section: Study Populationmentioning
confidence: 99%